1329. Burden of Respiratory Syncytial Virus (RSV) Infection among Hospitalized Older Adults and Those with Underlying Chronic Obstructive Pulmonary Disease (COPD) or Congestive Heart Failure (CHF). (4th December 2021) - Salazar, Luis W; Tippett, Ashley; Hussaini, Laila; Taylor, Megan; Reese, Olivia; Ciric, Caroline; Bristow, Laurel; Patel, Vikash; Li, Wensheng; Hsiao, Hui-mien; Stephens, Kathy; Gibson, Theda; et al.
Abstract: Background: The burden of Respiratory Syncytial Virus (RSV)-associated hospitalization in adults is incompletely understood. The COVID-19 pandemic has resulted in multiple public health measures (e.g., social distancing, handwashing, masking) to decrease SARS-CoV-2 transmission, which could impact RSV-associated hospitalizations. We sought to compare RSV-associated hospitalizations from 2 pre- and one mid-COVID-19 winter viral respiratory seasons. Methods: We conducted an IRB-approved prospective surveillance at two Atlanta-area hospitals during the winter respiratory viral seasons from Oct 2018–Apr 2021 for adults ≥ 50 years of age admitted with acute respiratory infections (ARI) and adults of any age with COPD or CHF-related admissions. Adults were eligible if they were residents of an 8 county region surrounding Atlanta, Georgia. Those with symptoms > 14 days were excluded. Standard of care test results were included. Asymptomatic adults ≥ 50 years of age were enrolled as controls in Seasons 1 and 2. Nasopharyngeal swabs from cases and controls were tested for RSV using BioFire® FilmArray® Respiratory Viral Panel (RVP). We compared the demographic features and outcomes of RSV+ cases and controls. Results: RSV was detected in 71/2, 728 (2.6%) hospitalized adults with ARI, CHF, or COPD and 4/466 (0.9%) controls. In Season 1, RSV occurred in 5.9% (35/596 patients), in Season 2 3.6% (35/970 patients), but in only 0.09% (1/1, 162 patients) in Season 3 (P < 0.001 for both seasons). RSV detection in Season 3 was similar to RSV detection among controls during Seasons 1 and 2 (P=0.6). Median age of cases and controls was 67 years (Table 1). Of cases with RSV 11% were admitted to the ICU and two required mechanical ventilation. The majority of hospitalized patients were discharged home (95.8%) with a median length of hospitalization of three days (IQR 2-7). Table 1. Demographic Features and Outcomes Among RSV-Positive Hospitalized Adults. Conclusion: Over 3 seasons, RSV was detected in 2.6% of adults admitted to the hospital with ARI, CHF or COPD. The rate of RSV dramatically declined during the 2020-21 winter respiratory viral season, likely due to public health measures implemented in response to COVID-19. Disclosures: David L. Swerdlow, MD, Pfizer Vaccines (Employee) Robin Hubler, MS, Pfizer Inc. (Employee) Larry Anderson, MD, ADVI (Consultant)Bavarian Nordic (Consultant)Novavax (Consultant)Phizer (Grant/Research Support, Scientific Research Study Investigator)Sciogen (Research Grant or Support) Christina A. Rostad, MD, BioFire Inc, GSK, MedImmune, Micron, Janssen, Merck, Moderna, Novavax, PaxVax, Pfizer, Regeneron, Sanofi-Pasteur. (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support)Meissa Vaccines (Other Financial or Material Support, Co-inventor of patented RSV vaccine technology unrelated to this manuscript, which has been licensed to Meissa Vaccines, Inc.) Nadine Rouphael, MD, pfizer, sanofi, lily, quidel, merck (Grant/Research Support) Nadine Rouphael, MD, Lilly (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Merck (Individual(s) Involved: Self): Emory study PI, Grant/Research Support; Pfizer: I conduct as co-PI the RSV PFIZER study at Emory, Research Grant; Pfizer (Individual(s) Involved: Self): Grant/Research Support, I conduct as co-PI the RSV PFIZER study at Emory; Quidel (Individual(s) Involved: Self): Emory Study PI, Grant/Research Support; Sanofi Pasteur (Individual(s) Involved: Self): Chair phase 3 COVID vaccine, Grant/Research Support Evan J. Anderson, MD, GSK (Scientific Research Study Investigator)Janssen (Consultant, Scientific Research Study Investigator, Advisor or Review Panel member)Kentucky Bioprocessing, Inc (Advisor or Review Panel member)MedImmune (Scientific Research Study Investigator)Medscape (Consultant)Merck (Scientific Research Study Investigator)Micron (Scientific Research Study Investigator)PaxVax (Scientific Research Study Investigator)Pfizer (Consultant, Grant/Research Support, Scientific Research Study Investigator)Regeneron (Scientific Research Study Investigator)Sanofi Pasteur (Consultant, Scientific Research Study Investigator)